Smoking Rationalisation, Tobacco Dependence and Intention to Quit Among Indian Adults and Adolescents - Pratibha Taneja; Shourya Tandon; Charu Mohan Marya; Ruchi Nagpal; Sakshi Kataria (Wolters Kluwer Medknow Publications, 2022)
Introduction: Unfortunately, indicators of tobacco dependence are present even after low levels of exposure in young smokers. Early emergence of these signal risk for subsequent chronic smoking and nicotine dependence is negatively associated with cessation in young adults. One important yet understudied modifiable predictor of intention to quit among smokers is smoking rationalization. Smokers often subscribe to smoking rationalisation beliefs, also known as self-exempting beliefs, to justify or rationalize their smoking behaviors. Smoking rationalizations can predict a lack of intention to quit. Objective: To assess the correlation between smoking rationalisation, tobacco dependence and intention to quit among Indian adults and adults. Methodology: A cross-sectional pilot study was carried out among 18-60-year-old subjects. Data were collected for tobacco dependence, smoking rationalisation and intention to quit (no/yes) by structured interview. Data were analysed using IBM SPSS statistics for windows, version 16 (IBM Corp, Armork, NY.) The independent t-test and one way ANOVA and binary logistic regression were performed for inferential statistics. Results: Smokers with no intention to quit and high tobacco dependence scores had significantly higher smoking rationalisation than those to quit and low dependence scores. Logistic regression models demonstrated that all types of rationalisation beliefs were consistently inversely associated with the intention to quit and low tobacco dependence. Conclusion: Findings suggest that smoking rationalisation plays an important role in the lack of intention to quit among Indian smokers. Future interventions should tackle smoking rationalisation beliefs as a strategy to promote smoking cessation.